Peoples of the River Valleys : The Odyssey of the Delaware Indians - Schutt, Amy C. (Book collections on Project MUSE., 2007)
Offers a fresh interpretation of the history of the Delaware, or Lenape, Indians in the context of events in the mid-Atlantic region and the Ohio Valley.